Humeral shaft fractures in adults: management and evaluation of treatment in 50 cases - Camara, Abdoulaye; Camara, Nouhou M.; Diallo, Mamadou M.; Lamah, Léopold (International Surgery Journal, 2024)
Background: The management of humeral shaft fractures is a real challenge in our regions. Methods: This was a prospective, descriptive single-center study involving 50 patients meeting our inclusion criteria. Inclusion criteria focused on adult patients, received for fractures of the humeral shaft, treated and followed up, then evaluated during the study period. Exclusion criteria included humeral shaft fractures in children, patients not having been evaluated during the study period. Results: We enrolled 50 patients, 43 men (86%) and 7 women (14%), with a sex ratio of 3.07. Mean age was 32.3 years, with extremes of 18 and 79 years. The left side was affected in 46 cases (92%). Lesions were predominantly located in the middle 1/3 in 39 cases (78%). Treatment was orthopedic in 30 patients (60%). Surgical treatment was performed in 20 patients (40%), with screw-plate predominating in 14 cases (28%), followed by hackethal pinning in 5 cases (10%) and combined treatment in one case (2%). At six months' follow-up, our results were very good and good in 36 cases (72%) according to the modified Stewart and Hundley functional score. Conclusions: Humeral shaft fractures are rare fractures for which orthopedic treatment is still indicated. Complications include radial nerve paralysis and pseudarthrosis.